The football movement profile of youth national team players - Szigeti, G.; Schuth, G.; Kovacs, T.; Pavlik, G.; Barnes, C. (Sport Performance & Science Reports, 2021)
The Football Movement Profile (FMP) is a new sport specific movement algorithm developed by Catapult Sports (Catapult Sports, Melbourne, Australia), to provide deeper insight into the true demands of football training and match play. The algorithm groups movement characteristics by type and intensity into 6 categories which can be both represented in absolute (total duration) and relative (percentage duration) terms. This could help coaches and practitioners to better understand the load characteristics of players in training and match-play scenarios.